The influence of dimethyl sulfoxide (DMSO) on metabolic activity and morphology of melanoma cell line WM-266-4 - Ferk, Polonca; Dariš, Barbara (Cellular and Molecular Biology, 2018)
Dimethyl sulphoxide (DMSO) is widely used as a solvent in biomedical research, regularly in concentrations up to 1%. Nevertheless, little is known about the effect of different DMSO concentration on WM-266-4 metastatic melanoma cells, which are often used in melanoma research. Due to resistance of melanoma cells high concentrations of cytotoxic substances soluble in DMSO are used in vitro tests. Consequently, total DMSO concentration often exceeds 1%. The aim of our study was to test the metabolic activity and morphology of WM-266-4 cells exposed to selected DMSO concentrations for different period of time. Cells were incubated in selected ethanol concentrations for comparison. MTT test was performed to determine proliferation activity of the cells and morphological analysis was carried out by phase-contrast microscopy. Our results show inhibitory effect of DMSO on WM-266-4 cells’ metabolic activity. Morphology of the cells changed progressively with the time of exposure. Ethanol showed little effect on metabolic activity of the cells and no effect on cell morphology after selected period of time. According to our study, for specific in vitro tests concentrations of DMSO up to 1.5% may be appropriate for WM-266-4 cell line experiments.